Pembelajaran Pendidikan Agama Islam (PAI) Model Keberagamaan Inklusif untuk Mencegah Radikalisme Beragama Dikalangan Siswa SMA - Abdurrohman Abdurrohman; Huldiya Syamsiar (FENOMENA, 2017)
The phenomenon of religious radicalism has become a global threat of the 21st century that phenomenon was a result of Islam as anaccused religion and was often associated with a terrorist religion. Educational institutions often "suspected" in creating of terrorists’ generations because the content material of Islamic Religious Education Study was dogmatic, indoctrinated, and related to proselytizing spirit that confirms truth claims. Anyway, substance of instructional materials used in senior high school does not contain inclusive religious content so it can create an exclusive and intolerant religious behavior among senior high school students. The aim of this study; 1).Providing foothold among students of theological and sociological thinking and behavior in order to have an inclusive and tolerant religiosity 2).Deploying and seeding ideas and behavior of an inclusive and tolerant religiosity as a form of resistance ideology (de-radicalization). 3). Filling the void literature Islamic Religious Education Study particular model of inclusive diversity relevant to mainstream Islam in Indonesia. To counteract the religious radicalism among students, the teaching material of Islamic Religious Education Study must contain religious inclusive content incorporating the teachings of Islam as a religion Rahmatan Lil Alamin, a religion of tolerance which is supported by the argument of the Quran and hadith. By using this model of teaching materials is expected of senior high school students have an inclusive religious behavior that is relevant to the character and Indonesian Islam mainstream in order to prevent radicalism behavior among senior high school students.